2020
DOI: 10.1038/s41598-020-68297-4
|View full text |Cite
|
Sign up to set email alerts
|

Combining stochastic models of air temperature and vapour pressure for the analysis of the bioclimatic comfort through the Humidex

Abstract: Several studies evidenced the importance of the knowledge of the bioclimatic comfort for improving people's quality of life. temperature and relative humidity are the main variables related to climatic comfort/discomfort, influencing the environmental stress in the human body. In this study, a stochastic approach is proposed for characterizing the bioclimatic conditions through the Humidex values in six sites of calabria (southern italy), a region often hit by heat waves in summer months. the stochastic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Several studies indicated the different influence of temperature and relative humidity on the Humidex behavior, showing that the discomfort conditions are significantly related to air temperature, while the impacts of humidity are of less importance [46]. Within this context, a preliminary analysis focused only on temperature trend data in the period 2001-2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicated the different influence of temperature and relative humidity on the Humidex behavior, showing that the discomfort conditions are significantly related to air temperature, while the impacts of humidity are of less importance [46]. Within this context, a preliminary analysis focused only on temperature trend data in the period 2001-2017.…”
Section: Resultsmentioning
confidence: 99%
“…The territory, in fact, has a mainly flat conformation and it is crossed by the longest river in Calabria. Moreover, Sirangelo et al [46] evidenced the different influence of temperature and relative humidity on the Humidex behavior. Finally, in the Crati River valley is Cosenza, the fifth Calabrian city by number of inhabitants, which hosts one of the four Hospital Hubs, able to provide specialist diagnostic and therapeutic services, of the Calabria Region.…”
Section: Introductionmentioning
confidence: 99%
“…The data were analysed using Microsoft Excel and the focus was on ambient temperatures, humidity, humidex and apparent temperatures. Humidex (Hum) and apparent temperatures (AT) were used due to their wide application both locally in South Africa (Garland et al 2015 Humidex is calculated using local ambient temperatures and saturated vapour pressure, based on a method developed by Sirangelo et al (2020). This study calculated humidex using dry bulb temperature and relative humidity: As noted in equations (1-3), Hum is calculated using ambient temperature (Ta) (°C), and calculating the water vapour pressure (e) using the relative humidity (Ur) and Ta based on Teten's formula (Sirangelo et al 2020).…”
Section: Analysis Of Findingsmentioning
confidence: 99%
“…Although it is not a perfect heat stress indicator, it is convenient to use in contexts with data limitations as it only requires air temperature and relative humidity. The wet-bulb, drybulb temperatures and relative humidity were used to derive the saturated vapour pressure employed in the humidex calculations as developed by Sirangelo et al (2020).…”
Section: Sasbementioning
confidence: 99%